SnO2 modified PNN-PZT ceramics with ultra-high piezoelectric and dielectric properties. Issue 16 (15th August 2022) - Guo, Feifei; Zhang, Shaokun; Long, Wei; Fang, Pinyang; Li, Xiaojuan; Xi, Zengzhe
Abstract: In this work, a two-step solid-state reaction method is used to prepare the 0.55 Pb(Ni1/3 Nb2/3 )O3 -0.135PbZrO3 -0.315PbTiO3 / x SnO2 (PNN-PZT/ x SnO2 ) ceramics. The influences of SnO2 on the crystalline structure, electromechanical properties, and temperature stability of PNN-PZT ceramics were studied in detail. The results demonstrate that the Sn 4+ ions are successfully introduced into the PNN-PZT crystalline lattice and substitute B-site Ni 2+ and Zr 4+ . The x  = 0.0025 ceramic with the coexistence of rhombohedral, tetragonal, and pseudocubic phases exhibits the optimized comprehensive properties: the quasi-static piezoelectric constant d 33, large-signal d 33 *, electromechanical coupling coefficients k p and k t, free dielectric constant ε r, and mechanical quality factor Q m are 1123 pC/N, 1250 p.m./V, 0.63, 0.54, 9529, and 57, respectively. Meanwhile, the Curie temperature for this composition is 103 °C, almost maintaining the same level as the PNN-PZT matrix. After annealing at 75 °C, the retained d 33 of x  = 0.0025 ceramic is as high as 975 pC/N, superior to the PNN-PZT matrix (retained d 33  ≈ 873 pC/N). Our results provide a promising piezoelectric material for board bandwidth, high sensitivity, and miniaturized medical ultrasonic transducers applications.